Piezoelectric Battery Charger - Mat Zian @ Mat Zin, Ahmad Faiz; Mantari, M.H.A.R.; M.H.A.R., Roslan; M. S., Azahan; Aziz, N.I.N.A.; Daud, N.L.M. (Multidisciplinary Applied Research and Innovation, 2024)
Piezoelectric Battery Charger is an alternative rechargeable battery that uses mechanical vibrations to apply strain energy to the piezoelectric material. This hallmark meets the standard of environmental responsibility as it creates less waste. This project aims to design and fabricate a free energy battery charger that inspects the voltage output based on the number and arrangements of piezoelectric plates used and the effects on the shape and material of the pusher up and pusher down. The product development includes inserting dimensions for machine components in SolidWorks, material selection, fabrication, 3D printing, assembly and testing for results and discussions. The performance of alternating current voltage output was between 0.5 V to 3.9 V from the test implemented by using a washing machine. By using the concept of electricity accumulation, the battery can store unused energy for later needs.